An updated perspective on immunoglobulin replacement in chronic lymphocytic leukaemia in the era of targeted therapies - Khan, Sujoy; Allsup, David; Molica, Stefano (Frontiers in Oncology, 2023)
Chronic lymphocytic leukaemia (CLL) is a malignancy of clonally expanded antigen-switched, neoplastic, mature B cells. CLL is characterised by a variable degree of immunosuppression and secondary hypogammaglobulinemia. B-cell depleting therapies have historically been deployed with a proportion of patients becoming resistant to multiple lines of treatment with an associated worsening of immunosuppression and heightened infection risk. Advances in molecular diagnostics and the development of new therapies targeting Bruton’s tyrosine kinase and B-cell lymphoma-2 have resulted in novel insights into the cellular mechanisms associated with an increased infection risk and T-cell escape from the complex tumour environment found in CLL. Generally, immunoglobulin replacement therapy with polyvalent human immunoglobulin G (IgG) is indicated in patients with recurrent severe bacterial infections and low IgG levels, but there is no consensus on the threshold IgG level for initiation of such therapy. A proportion of CLL patients have residual IgG production, with preserved quality of the immunoglobulin molecules, and therefore a definition of ‘IgG quality’ may allow for lower dosing or less frequent treatment with immunoglobulin therapy in such patients. Immunoglobulin therapy can restore innate immunity and in conjunction with CLL targeted therapies may allow T-cell antigen priming, restore T-cell function thereby providing an escape from tumour-associated autoimmunity and the development of an immune-mediated anti-tumour effect. This review aims to discuss the mechanisms by which CLL-targeted therapy may exert a synergistic therapeutic effect with immunoglobulin replacement therapy both in terms of reducing tumour bulk and restoration of immune function.